Chicagská škola a česká sociologie - Musil, Jiří (Lidé města, 2012)
Czech sociology in the period since 1925 has reacted to the Chicago School in four ways: (1.) The first type of reaction was represented by a group of authors who either dismissed this approach or ignored it completely; (2.) The second reaction was represented by sociologists who knew about the approach and basically referred to it in a neutral manner; (3.) The third reaction were attempts to interpret the School in the deeper context of the development of American sociology in the first half of the 20th century; this reaction included both criticism and positive acknowledgment; (4.) The fourth reaction essentially varies. Its common factor is the acceptance of the basic theoretical or merely methodological tenets of the School. They intentionally continued in the tradition of the Chicago School, and often complemented or otherwise modified its approaches. All four of these reaction types stemming from the Czech environment reacted chiefly to the Chicago School’s concept of urban sociology, and less to its urban ethnology and social psychology.